Analisis Kerentanan Keamanan Data Pada BAPELITBANG SUMUT: Upaya Penguatan Perlindungan Informasi - Prananda, Dimas Raka; Nasution, Yusuf Ramadhan; Prayoga, Dio (Journal Of Informatics And Busisnes, 2023)
The utilization of information technology inside the Research and Development Agency of North Sumatra (BAPELITBANG SUMUT) has a significant impact on data security. The objective of this study is to evaluate the issue of data security at the Research and Development Agency of North Sumatra (BAPELITBANG SUMUT) and propose solutions to enhance data security. Infrastructure technology, security policies, access management, and user awareness are components of vulnerability identification. Dalam rangka memperoleh pemahaman yang komprehensif mengenai tingkat efektivitas tindakan keamanan yang telah dilaksanakan, diperlukan suatu evaluasi terhadap system keamanan yang sedang berjalan. In addition, the study assesses the extent to which BAPELITBANG SUMUT complies with the applicable security regulations. This study provides a foundation for enhancing data security comprehensively by designing and implementing efforts to improve information protection, such as security policy updates, infrastructure enhancements, and user training. Pengujian dan evaluasi implementasi upaya penguatan digunakan untuk menilai tingkat efektivitasnya. The objective of this study is to provide guidance for similar institutions in enhancing their data security and contribute to the literature on local government data security management. The results indicate that measures to enhance data security are necessary to ensure the integrity, confidentiality, and availability of data managed by BAPELITBANG SUMUT..